2013
DOI: 10.1179/2045772313y.0000000149
|View full text |Cite
|
Sign up to set email alerts
|

Modification of spasticity by transcutaneous spinal cord stimulation in individuals with incomplete spinal cord injury

Abstract: Participants: Three subjects with chronic motor-incomplete spinal cord injury (SCI) who could walk ≥10 m. Interventions: Two interconnected stimulating skin electrodes (Ø 5 cm) were placed paraspinally at the T11/T12 vertebral levels, and two rectangular electrodes (8 × 13 cm) on the abdomen for the reference. Biphasic 2 mswidth pulses were delivered at 50 Hz for 30 minutes at intensities producing paraesthesias but no motor responses in the lower limbs. Outcome measures: The Wartenberg pendulum test and neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
172
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(178 citation statements)
references
References 47 publications
5
172
1
Order By: Relevance
“…15,16 It has been shown that the remaining altered spinal cord circuits below the injury can be activated and modified by transcutaneous spinal cord stimulation. 17 We suppose that in patients in whom the vestibulospinal pathways remained preserved, the altered spinal cord circuits below the injury could be conditioned by activation of the vestibulospinal pathways. To confirm this assumption, additional experimental work must be done.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 It has been shown that the remaining altered spinal cord circuits below the injury can be activated and modified by transcutaneous spinal cord stimulation. 17 We suppose that in patients in whom the vestibulospinal pathways remained preserved, the altered spinal cord circuits below the injury could be conditioned by activation of the vestibulospinal pathways. To confirm this assumption, additional experimental work must be done.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 It has been shown that the remaining altered spinal cord circuits below the injury can be activated and modified by transcutaneous spinal cord stimulation. 17 We …”
mentioning
confidence: 99%
“…The active electrode consisted of two self-adhesive electrodes (ø 5 cm, V.Trodes, Mettler Electronics Corp., USA) connected together over the intervertebral space T11-T12. Analogously, the indifferent electrode consisted on two electrodes (7.5 × 13 cm, ValuTrode, Axelgaard Manufacturing Co., Ltd., USA) placed symmetrically over the umbilicus [5]. The stimulation protocol consisted in biphasic currentcontrolled stimulation continuously applied for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Alternative treatments have been proposed applying electrical stimulation via epidural [4] and transcutaneous electrodes [5,6]. These studies suggest that an electrical field induced over the spinal cord is able to selectively depolarize the posterior root fibers in the lumbosacral region, leading to the activation of inhibition mechanisms as the Ia inhibitory interneurons and the increase of descending inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation